Does the COVID-19 pandemic have influenced the profile of primary bloodstream infections in critically ill neonates? - Souza Junior, Helio de; Ribeiro, Zilka dos Santos de Freitas; Carvalho, Jeane Kelly Silva de; Silva, Priscila Stephanny Penha da; Conceição, Thatiane Ferreira da; Hermann, Paula Regina de Souza (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: Primary Bloodstream Infection (PBSI) associated with Central Venous Catheters (CVC) is the primary site of healthcare-associated infections in Neonatal Intensive Care Units (NICUs). Aim: To assess the occurrence of PBSI associated with Peripherally Inserted Central Catheters (PICC) in neonates, before and during the COVID-19 pandemic. Outlining: We conducted a retrospective cohort analysis in the NICU of a teaching hospital in the Federal District, Brazil. The sample included 169 neonates who used PICCs from 2018 to 2021. Results: There were 16 primary bloodstream infections, with 50% occurring in the pre pandemic period and 50% during the pandemic. Additionally, 267 blood cultures were performed, of which 17.23% were positive, including 61.7% gram-positive microorganisms and 36.17% gram-negative. The primary microorganisms identified were Klebsiella spp. and coagulase-negative Staphylococcus, with one microorganism exhibiting oxacillin resistance. Implications: We emphasize the importance of monitoring and maintaining continuous surveillance of PBSI associated with CVC, especially during events like the COVID-19 pandemic. Stringent infection control measures should be implemented to minimize the risk of infection and improve care in neonatal intensive care units.